LABOR ABSORPTION OF THE FOOD CROPS SUB-SECTOR IN THE NEW NORMAL ERA IMPACT OF THE COVID19 PANDEMIC OUTBREAK (Case Study: Kapuk Village, Tabir Ulu District, Merangin Regency) - Fikriman, Fikriman; Putri, Cahyani; Susilawati, Widuri; Is, Asnawati; Isyaturriyadhah, Isyaturriyadhah; Pitriani, Pitriani; Afrianto, Evo; Suryani, Lili; Setiono, Setiono; Febrialdi, Akhyarnis (Universitas 17 Agustus 1945 Samarinda, 2025)
This research was carried out in Kapuk Village, Tabir Ulu District, Merangin Regency from 30 January to 30 February 2020 with the aim of (1) The Large Contribution of Labor to the Food Crops Sub Sector in the New Normal Era. The Impact of the COVID-19 Pandemic Outbreak (2) multiple times to determine the influence of productivity labor and wage levels in labor absorption in the food crop sub-sector The method for determining the sample was carried out purposively. The sampling technique is simple random sampling. Contribution data uses contribution analysis to determine the magnitude of the contribution of labor in the food crop sub-sector to the agricultural sector. To find out the magnitude of the contribution of labor in the food crop sub-sector to the entire sector, the data used in this research is secondary data from the village office and multiple linear regression to determine the influence labor productivity and wage levels in the employment of the food crop sub-sector and the data used is primary data..The results of this research are (1) The contribution of labor in the food crop sub-sector to the agricultural sector is 55.10% with a very good category including: the number of workers in the food crop sub-sector and the number of workers in the agricultural sector in Kapuk Village, Tabir Ulu District, Merangin Regency. (2) The contribution of labor in the food crops sub-sector to the entire sector is 53.65% with a very good category including: the number of workers in the food crops sub-sector and the number of workers in the entire sector (3) Labor Absorption (Y) is partially influenced by labor productivity X1, namely with a value of tcount 4.035< ttable 1.999. and simultaneously labor absorption is also influenced by labor productivity female labor wages (X3) have no effect on the dependent variable labor absorption (Y) because they have the same value.